PEMBELAJARAN DARING UNTUK MENDUKUNG IMPLEMENTASI MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Utari Dewi; Alim Sumarno; Lamijan Hadi Susarno (Kwangsan: Jurnal Teknologi Pendidikan, 2022)
The purpose of this study was to determine the effectiveness of bold learning tools for Model Development and Reality courses in the form of semester learning plans (RPS), media, and learning materials. This learning tool will be used by students who collaborate on student exchanges in order to support the implementation of Merdeka Belajar Kampus Merdeka (MBKM) in higher education. This development uses the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) model. The results of the test using learning tools were declared very good by material experts (100%) and media experts (91.67%). Likewise with the results of trials conducted on students as user samples. Users say the results are very good (90%). Meanwhile, the effectiveness of this research product can be proven by the test scores achieved by the experimental class students. The results of the A test reached 86.4% of the experimental class students and 57.2% of the control class students. In conclusion, it can be stated that this product applies the principles used and is effectively used for bold learning. Considering that the resulting product is easily accessible and user friendly, it will be able to support the implementation of merdeka belajar kampus merdeka AbstrakTujuan penelitian ini adalah untuk mengetahui kelayakan dan keefektifan perangkat pembelajaran daring untuk mata kuliah Pengembangan Model dan Realia berupa rancangan pembelajaran semester (RPS), media, dan bahan pembelajaran. Perangkat pembelajaran ini akan digunakan secara daring oleh mahasiswa yang melakukan kerjasama pertukaran pelajar dalam rangka mendukung implementasi Merdeka Belajar Kampus Merdeka (MBKM) di Pendidikan tinggi. Pengembangan ini menggunakan model ADDIE (Analyze, Design, Develop, Implement, and Evaluate). Hasil uji kelayakan perangkat pembelajaran dinyatakan sangat baik oleh ahli materi (100%) dan ahli media (91,67%). Demikian juga dengan hasil uji coba yang dilakukan kepada mahasiswa sebagai sampel pengguna. Pengguna menyatakan hasilnya sangat baik (90%). Sedangkan keefektifan produk penelitian ini dapat dibuktikan dengan nilai hasil tes yang dicapai mahasiswa kelas experimen. Hasil tes nilai A dicapai 86,4% mahasiswa kelas eksperimen dan 57,2% mahasiswa kelas kontrol.  Sebagai kesimpulan dapat dikemukakan bahwa produk ini memenuhi kaidah-kaidah kelayakan dan efektif digunakan untuk pembelajaran daring. Mengingat produk yang dihasilkan ini mudah diakses dan user friendly maka akan dapat mendukung implementasi program merdeka belajar kampus merdeka.